Impacts of diversified repetition on multilevel motor organization during piano performance - Monteiro, Paloma; Gentili-Morin, Maxwell; Gatti, Giordano; Casarotti, João Paulo; Fagundes Loss, Jefferson; M. Wanderley, Marcelo; Antunes Teixeira dos Santos, Regina (ANPPOM, 2026)
Abstract. This study investigates the effects of diversified repetition practice on pianists’ bimanual coordination by comparing performances before and after a practice session involving variations in rhythm, articulation, dynamics, and tempo. Two pianists, identified as P1 and P2, participated in the study by performing the F major pentatonic scale across three phases: pre-test, practice, and post-test. Audiovisual recordings, MIDI data, and motion capture data were used to analyze the movements of fingers, wrists, and elbows. Three dimensions of performance were examined: note onset asynchrony (temporal synchronization), preparatory gesture amplitude (motor planning), and key attack velocity (dynamics). Motor strategies in proximal segments were also observed, focusing on patterns of symmetry, phase, and amplitude. The results revealed distinct responses between participants and across different note combinations. In some cases, increased simultaneity and gestural reorganization were observed; in others, there was a reinforcement of pre-existing patterns. The findings suggest that diversified repetition may promote subtle adjustments, motor stabilization, and the intensification of already established interpretive strategies. It is concluded that its effects arise from the interaction among technical, motor, and expressive factors, and that its application is most effective when tailored to the specific needs of each performer.